Prospective study on the use of technology and lean thinking in healthcare - Araujo, Andressa Clara Barbosa de; Pimentel, Cristiane Agra (Brazilian Journal of Production Engineering, 2024)
The complexity of healthcare units challenges the sector to manage its resources in order to deliver a safe and quality service. In this sense, the Lean philosophy is successfully applied, at the same time as we see an increase in the use of 4.0 enabling technologies. However, there are limitations in the knowledge of research on the topics covered together, requiring an investigative and prospective study on the topic. Thus, the objective of this research is to investigate the use of technology and Lean Thinking in the health area, through a scientific prospecting study using bibliometric analysis in the Pubmed, Lens and Dimensions databases as a method, with a time frame between 2014 and 2023, using the keywords: (“Lean” OR “Lean Thinking” AND “health 5.0” OR “health 4.0” OR “healthcare” AND “technology”). For the study, the VOSviewer software was used as an analysis tool. As a result, the authors and organizations with the greatest impact in the field of literature were obtained, with emphasis on organizations of Asian origin; in addition to the most frequently occurring keywords in the documents used, these being “human”, “health care provision” and “artificial intelligence”. Through the research, the trend of the relationship between the Lean philosophy and the use of technology in health was demonstrated, and its relevance for other studies.